Venture capital and initial public offerings: the prospects and impediments in African markets - Nage, Lerato (My University, 2013)
The aim of this study is to present venture creation as an alternative form of alleviating poverty and contributing positively to the economic growth of every African government. This study draws to the attention of policy-makers, the importance of venture creation in emerging economies. The author goes on further to highlights the challenges with the current models used for financing/funding new ventures, in an emerging African economy. The objective of this paper is to also highlight what needs to be done by policy-makers, to create a thriving economic environment for emerging entrepreneurs. This study seeks to highlight some of the prospects, as well as some of the impediments, experienced by the venture capital industry and start-up enterprises. The environment in which the creation of new ventures operates under in emerging African markets is reviewed, and the exit of those enterprises when they mature and graduate from a small, private company, to a publicly held company - through an Initial Public Offering (IPO) process, is examined. The benefits of exiting these ventures through an IPO, versus the more aptly applied private placement exit method, are also discussed. The impact that the behaviour and psychology of investing have on the investment trends in African economies is also discussed. The author used the qualitative research methodology to achieve the results presented in this paper. The outcomes of the study are outlined in chapter four of this paper. The respondents to the survey indicated the importance of the venture capital sector and the critical role that policy makers should be playing. There were no clear responses around the human behaviour in determining the suitable exit platform. What came out clearly in this study; was that each region in the African economy will use a different exit platform driven mainly by the economic environment. The author goes on further to conclude on the outcomes of the study and suggest further research on the topic on venture capital and initial public offerings. The participants who responded to the survey agreed with the literature reviewed, in particular around the adequate form of financing for starting up new enterprises.
Keywords: Initial public offerings; Venture capital; Small and medium enterprises; Entrepreneurship; Microfinance